THE IMPACT OF SUBJECTIVE NORMS ON THE BUYING INTENTION OF NON-MUSLIM CONSUMERS ON HALAL FOOD PRODUCTS IN SURABAYA - Nur Adila Wulandari; Ririn Tri Ratnasari (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of subjective norms on the buying intentions of non-Muslim consumers on halal food products in Surabaya. This study uses a quantitative approach. Data collection techniques are by distributing online questionnaires to 75 respondents who are non-Muslim domiciled in Surabaya and are at least 17 years old. The analysis technique used is Regression. The sampling method is conducted using a purposive sampling technique. The results of this study indicate that subjective norms have a significant positive relationship with purchase intention.Keywords: Halal Food, Subjective Norms, Behavioral Control, Purchase IntentionREFFERENCE Ahmad, A.N., Rahman, A.A., dan Rahman, S.A. (2015). Assessing knowledge and religiosity on consumer behavior towards halal food and cosmetic products. International Journal of Social Sciene and Humanity, 5(1), 10-14.Aziz, Y.A. and Chok, N.V. (2013). The role of halal awareness, halal certiﬁcation, and marketing components in determining halal purchase intention among non-Muslims in Malaysia: a structural equation modeling approach. Journal of International Food and Agribusiness Marketing, 25(1), 1-23.Fishbein, M. and I. Ajzen. (1975). Belief, attitude, intention, and behavior: An introduction to theory and research. Massachusetts: Addison-Wesley Publishing Company.Haque, A., Sarwar, A., Yasmin, F., Tarofder, K. and Hossain, M. (2015). Non- muslim consumers’ perception toward purchasing halal food products in Malaysia. Journal of Islamic Marketing, 6(1), 133-147.https://kumparan.com/atu-yudhistira/sertifikasi-halal-di-inggris-menggali-potensi-pasar-produk-halal-1553438206612711268.Kementerian Pendidikan Dan Kebudayaann Republik Indonesia. (2017). Pendidikan Agama Islam dan Budi Pekerti. Jakarta: Kementrian dan Kebudayaan.Krishnan, S., Aderis, M.H.H.M., Azman, M.N. and Kamaluddin, M.N.A. (2017). Halal food: Study on non muslim acceptance. American Journal of Economics, 7(1), 41-45.Malebana, M.J. & E. Swanepoel. (2015). Graduate entrepreneurial intentions in the rural provinces of South Africa. Department Of Management And Entrepreneurship, 19(1), 89-111.Wilson, JAJ dan Grant, J. (2013). Islamic marketing – a challenger to the classical marketing canon?. Journal of Marketing Islam, 4(1), 22-50.Zailani,S.,Kanapathy,K.,Iranmanesh,M. and Tieman, M. (2015). Drivers of halal orientation strategy among halal food ﬁrms, British Food Journal, 117(8), 2143-2160.